2018
DOI: 10.1002/jcp.27916
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA uc.294 is upregulated in early‐onset pre‐eclampsia and inhibits proliferation, invasion of trophoblast cells (HTR‐8/SVneo)

Abstract: Recently, a large number of long noncoding RNAs (lncRNAs) have been reported in human diseases that are evolutionarily conserved and are likely to play a role in many biological events including pre‐eclampsia. In our previous research, we selected thousands of lncRNAs for their relationship with early‐onset pre‐eclampsia. Among these lncRNAs, a lncRNA named uc.294 attracted our attention, was once reported to specifically be expressed at a high level in the early‐onset of pre‐eclampsia. This study aims to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“… [ 184 ] Uc.294 placenta upregulated / Uc.294 inhibits proliferation, invasion and promotes apoptosis of trophoblast cells HTR-8/SVneo. [ 185 ] PSG10P placenta upregulated miR-19a-3p/IL1RAP IL1RAP promotes the expression of caspase-3 but inhibits MMP9 to suppresses proliferation, migration, and invasion of trophoblast cells. [ 186 ] 00473 placenta downregulated LSD1/TFPI2 lnc00473 inhibits the expression of tissue factor pathway inhibitor 2 (TFPI2) through binding to lysine-specific demethylase 1 (LSD1) to inhibits cell proliferation and promotes apoptosis.…”
Section: Lncrnas and Pementioning
confidence: 99%
“… [ 184 ] Uc.294 placenta upregulated / Uc.294 inhibits proliferation, invasion and promotes apoptosis of trophoblast cells HTR-8/SVneo. [ 185 ] PSG10P placenta upregulated miR-19a-3p/IL1RAP IL1RAP promotes the expression of caspase-3 but inhibits MMP9 to suppresses proliferation, migration, and invasion of trophoblast cells. [ 186 ] 00473 placenta downregulated LSD1/TFPI2 lnc00473 inhibits the expression of tissue factor pathway inhibitor 2 (TFPI2) through binding to lysine-specific demethylase 1 (LSD1) to inhibits cell proliferation and promotes apoptosis.…”
Section: Lncrnas and Pementioning
confidence: 99%
“…Transwell invasion assay. Transwell assays were carried out as described previously (19). Cells (2x10 4 cells/well) were cultured at 37˚C for 24 h in 24-well plates with Transwell inserts precoated with Matrigel ® (37˚C for 30 min; BD Pharmingen; BD Biosciences).…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%
“…14 LncRNA SND1-IT1 can up-regulate POU2F1 to accelerate osteosarcoma proliferation and migration by sponging miR-665. 15 Studies have shown that lncRNAs, such as uc.294, 16 NR_002794, 17 CRNDE, 18 and TUG1, 19 are involved in PE development by affecting trophoblast functions. In the previous study, we detected lncRNAs specifically expressed in the placenta tissues of PE patients by using microarray assays.…”
Section: Introductionmentioning
confidence: 99%